Decision Support System For Determining Campus Promotion Media In New Student Admissions With Analytical Network Process And Regression Methods - Nur Iman; Supriadi Sahibu; Abdul Latief Arda (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2021)
Campus promotion is carried out in an effort to introduce the campus to the community, especially prospective new students. This effort was carried out as an action that was considered effective in recruiting new students. Various obstacles experienced by tertiary institutions in implementing campus promotion, namely the lack of need for supporting funds, limited human resources (HR), the right decision system for the selection of promotional media. This study analyzes the decision support system in selecting the right promotional media for campus promotion. The research objective is to assist campus management in selecting the right promotional media with a decision support system for determining the promotion media for new student admissions and determining the priority of the promotional media that will be used by private universities (PTS) in the city of Kendari. The sample in this study amounted to 40 respondents from 24 universities. The method used is the Analytical Network Process (ANP) method and the Regression method uses factor analysis. The results of the research analysis show that promotional media using the campus website has a number one rating, namely with a value of 26.2% while word of mouth has a second rating of 23.3%, then social media with a score of 23.1%, brochure 8.9%, print media and electronic media with a value of 6.2% and billboards have a value of 5.7%.